THE EFFECTIVENESS OF LEARNING USING THE USMANI METHOD AT TPQ BAABUSSALAAM - Surayanah, Surayanah; Zainudin, Mohammad; Kurniawan Barus, Yohannes; Lestariningsih, Lestariningsih (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
Background: Improving the quality of educational services is essential for enhancing learning outcomes through the implementation of effective teaching methods. One such method is the Usmani method, traditionally employed in the instruction of reading, writing, and memorizing the Al-Qur'an. Originating from early Islamic scholars, the Usmani method is increasingly being overshadowed, despite its potential to significantly enhance student learning outcomes. Purpose: This study aims to analyze the effectiveness of the Usmani method in the context of TPQ Baabussalaam. Method: The research employs a case study design with a qualitative descriptive approach, complemented by a quantitative analysis for data interpretation. Result: The findings indicate that the Usmani method has a substantial positive impact on student learning outcomes at TPQ Baabussalaam, as evidenced by measurable improvements in student performance. The stages of instruction following the Usmani method include the recitation of *Hadroh Fatihah*, prayer at the start of the lesson, preparation for students to engage with the material, repetition of previously learned content, explanation of new topics with examples, group training, individual training, and the delivery of moral messages, prayers, and greetings. Conclusion: The Usmani method proves to be an effective pedagogical approach, significantly enhancing student motivation and directly contributing to improved learning outcomes.